2020
DOI: 10.1177/2333794x20947982
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Posterior Tibial Nerve Block to Facilitate Foreign Body Removal in a School-Aged Child

Abstract: Ultrasound is increasingly becoming the standard of care for the detection and localization of radiolucent foreign bodies in the Emergency Department. How Does Your Research Contribute to the Field? We describe the technique for using point-of-care ultrasound to detect retained foreign bodies in the sole of the foot, and demonstrate that (posterior tibial) nerve blocks can be successfully performed in relatively young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…With the increasing availability and use of POCUS, regional anesthesia of the femoral nerve can be performed under real-time US guidance. Multiple case reports have shown US guidance to be effective in guiding nerve block administration in pediatric patients 10,11 . Ultrasound aids in the visualization of the needle tip and ensures accurate placement of the anesthetic bolus, which has been shown to improve the effect of analgesia 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing availability and use of POCUS, regional anesthesia of the femoral nerve can be performed under real-time US guidance. Multiple case reports have shown US guidance to be effective in guiding nerve block administration in pediatric patients 10,11 . Ultrasound aids in the visualization of the needle tip and ensures accurate placement of the anesthetic bolus, which has been shown to improve the effect of analgesia 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective randomized controlled trial in 60 pediatric forearm fracture patients demonstrated decreased pain scores and increased parent and operator satisfaction with use of an infraclavicular brachial plexus block compared with procedural sedation 20 . Additional smaller studies have demonstrated excellent pain control and patient satisfaction in patients who received forearm blocks for injuries of the distal upper extremity, 21,22 and several case reports have reported on the use of the popliteal block and posterior tibial nerve block for painful procedures of the distal lower extremity 23–25 …”
Section: Review Of the Literaturementioning
confidence: 99%
“…20 Additional smaller studies have demonstrated excellent pain control and patient satisfaction in patients who received forearm blocks for injuries of the distal upper extremity, 21,22 and several case reports have reported on the use of the popliteal block and posterior tibial nerve block for painful procedures of the distal lower extremity. [23][24][25] Saphenous nerve block has been used to aid in intraoperative and postoperative pain management for knee, lower leg, and ankle surgeries. Blockade of the SN can be accomplished at a variety of levels extending from the femoral nerve at the inguinal crease to the distal SN at the medial ankle.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…1,2 The PTN block is effective for pain control in distal foot amputations, surgeries, foot fractures, and foreign body removal. [3][4][5][6][7][8] In the civilian setting, the emergency department (ED) is often the first point of care for patients with frostbite, where there is a need for safe, effective, and timely management of frostbite injuries to prevent long-term consequences such as chronic pain, necrosis, and amputation. 9 This case series presents ED patients with frostbite on bilateral plantar surfaces who received posterior tibial nerve (PTN) blocks to facilitate Hennepin County Medical Center, Department of Emergency Medicine, Minneapolis, Minnesota University of Minnesota Medical School, Minneapolis, Minnesota * † debridement and wound care.…”
Section: Introductionmentioning
confidence: 99%
“…10 Previous studies have demonstrated the accessibility and effectiveness of PTN blocks for calcaneal fractures and foreign body removal in pediatric patients. [3][4][5][6] Nerve blocks at the stellate ganglion, lumbar epidural space, and at the distal nerve of the wrist have been shown to provide substantial pain relief prior to frostbite treatment. 1,2,11 To our knowledge there is no documented case of the PTN block used for frostbite management, despite its ease of application and historically high success rates for pain control.…”
Section: Introductionmentioning
confidence: 99%